JAK inhibitors: A new dawn for oral therapies in inflammatory bowel diseases - Herrera-deGuise, Claudia; Serra-Ruiz, Xavier; Lastiri, Ernesto; Borruel, Natalia (Frontiers in Medicine, 2023)
Inflammatory bowel disease (IBD) is a chronic immune-mediated condition of the gastrointestinal tract that requires long-term treatment and close monitoring. Over the past two decades, the development of new monoclonal antibodies targeting one or a few single cytokines, including anti-tumor necrosis factor agents, anti-IL 12/23 inhibitors, and antiα4β7integrin inhibitors, have dominated the pharmacological armamentarium in IBD. However, many patients experience inadequate response due to primary non-response or loss of response over time or develop severe adverse events that lead to drug discontinuation. Janus kinase (JAK) plays a crucial role in mediating the signal transduction pathway for many different proinflammatory cytokines that are directly involved in the pathogenesis of IBD by controlling intestinal inflammation. Targeting the JAK-STAT pathway offers excellent potential for the treatment of IBD. Tofacitinib and upadacitinib are approved for treating adults with moderately to severely active UC. The selective JAK1 inhibitors filgotinib and upadacitinib increased remission rates in patients with moderate to severe CD. Other JAK inhibitors, including gut-selective molecules, are complete or ongoing for UC and CD. This review will discuss the JAK-STAT pathway, its implication in the pathogenesis of IBD, and the most recent evidence from clinical trials regarding the use of JAK inhibitors and their safety in IBD patients.